Dynamic simulation of switched-reluctance motor using MATLAB/SIMULINK / Roslan Bakar - Bakar, Roslan (2003)
The dynamic simulation of the SR motor is fairly demanding in terms of computer resources. The introduction of SIMULINK from MathWorks greatly simplifies the task. In this work, the nonlinear flux-linkage versus current model of the SR motor is implemented as a m-file S-function using the MATLAB's two-dimensional interpolating function. The performance of a two-phase 4/6 pole SR motor is investigated. The simulation results for a simple current control considered to be reasonable but further work is required to implement control algorithm for accurate speed and torque control.